2012
DOI: 10.1103/physreva.85.023429
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton dissociation of HeH+below the He+(1s)+H(1s

Abstract: We discuss the strong-field dynamics of HeH + , the simplest stable heteronuclear molecule, focusing on identifying a laser regime for which there is a sufficient dissociation signal for experimental measurement. We numerically solve the time-dependent Schrödinger equation to obtain total dissociation probabilities, kineticenergy release spectra, and momentum distributions for wavelengths from 800 to 2400 nm. The suitability of this simple system as a prototype for understanding the strong-field nuclear dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
4
17
0
Order By: Relevance
“…The methods used for the solution will be outlined here, but are described in more detail in our previous work [44,48]. The electric field is treated classically, and the length gauge is used within the dipole approximation.…”
Section: A Born-oppenheimer Representation For the Time-dependent Scmentioning
confidence: 99%
See 2 more Smart Citations
“…The methods used for the solution will be outlined here, but are described in more detail in our previous work [44,48]. The electric field is treated classically, and the length gauge is used within the dipole approximation.…”
Section: A Born-oppenheimer Representation For the Time-dependent Scmentioning
confidence: 99%
“…In this paper, we will take advantage of the generality of the photon-phase representation to extend our under-standing of coherent control to a new system: HeH + , the simplest heteronuclear molecule with an electronic asymmetry in the standard Born-Oppenheimer approximation. We have previously shown [44] that exposing HeH + to long-wavelength pulses (longer than roughly λ = 2000 nm) produces dissociation probabilities that are large enough to realistically measure provided the intensity approaches I = 10 14 W/cm 2 . These relatively large dissociation probabilities, coupled with the fact that HeH + ion beams have been shown to be viable experimental targets [45][46][47], make both experimental and theoretical studies on CEP control of HeH + dissociation reasonable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large permanent dipole moment allows direct transfer of population from lower to higher vibrational states, which results in stretching of the molecule on the femtosecond timescale [13]. Electronic excitation, on the other hand, is negligible [20] due to the large energy difference between the electronic ground state X 1 Σ + and the first excited state A 1 Σ + , see Fig. 1.…”
mentioning
confidence: 99%
“…This is based on the intuition that the field-free rotational timescale of picoseconds is much greater than the vibrational timescale of fs and thus rotational motion can be safely neglected.However, as several works employing semiclassical methods [7,18,19] have shown, rotational dynamics are crucial for the understanding of the angular distribution of the final ion fragments. Even at lower intensities where ionization is negligible and pure dissociation is the dominating fragmentation process, it was shown that molecular rotations play a role [20][21][22][23][24] for pulses as short as ∼ 5 fs.For our studies, we choose to focus on the simplest stable polar molecule, HeH + , sketched in Fig. 1(d).…”
mentioning
confidence: 99%